(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2022)
A cochlear implant is a surgically implanted device used for hearing rehabilitation of adults and children with severe to profound sensorineural hearing loss and poor speech discrimination who gain limited benefit from conventional hearing aids. There is growing evidence that early application of a cochlear implant in children affected by profound hearing loss is of the greatest importance for the development of adequate auditory performance and language skills. The indication for cochlear implantation in children is bilateral sensorineural hearing loss > 80 dB determined on the basis of hearing tests. In congenital deafness, after completing diagnosis, the cochlear implant should be placed at the age of 12 months. When the desired outcome of cochlear implantation is to develop listening and spoken language skills, intensive speech and language therapy is necessary. Although services differ based on each child’s current level of performance, it is recommended that children receive auditory-based therapy after implantation to maximize benefit from the cochlear implant. Whatever approach is selected, rehabilitation after cochlear implantation is a long process. Parents and family members have a big role in development of spoken language of the child.